Research of Roman-period metallurgy: Remarks based on the chemical composition analyses of the eye brooches of the Prussian series from the burial ground in Malbork-Wielbark - Łuczkiewicz, Piotr; Gan, Paweł; Kleemann, Jörg; Kuzioła, Aneta (Sprawozdania Archeologiczne, 2022)
Analyses of the alloy composition of the 114 artefacts from 21 sites of the Wielbark and Przeworsk cultures indicate that these brooches largely correspond to the Roman categories of alloys. The most numerous group of brooches was made of an alloy type M – middle, that is the product of mixing new pure brass with scrap bronze. Such finds are most often found in the cemeteries of the Wielbark culture. Other items were made of metal type B, often found in Roman period artefacts. It is high in zinc content and created with the use of non-mixed brass. This smallest group in the analysed data set appears both in cemeteries of the Wielbark and Przeworsk cultures. Also quite prelevant were recycled alloys, obtained through melting together various raw materials (lower zinc content metal – type A). Most of such brooches are from the Mazovian sites. This may indicate the functioning of local workshops there, which worked using available, processed raw material.